Measures of Narration as a Method for Studying Aphasic Language - Ahlsen, Elisabeth (Journal of Modern Languages, 1996)
The aim of the present study is to describe some features of aphasics' narration and the development of these features over time (during nine months of rehabilitation). The features that are described here pertain to the area of factual content (i.e., the goal is to find out how much factual information is conveyed and how this is done).